Chapter 2 The Semiotics of Multimodality in Discourse - De Benedictis, Raffaele (Taylor & Francis, 2024)
In this study discourse is considered as the act of communication that analyzes its internal dynamic process mediating between the intention of the author embedded in the text, the intention of the text, and various, hypothetical ways in which the receiver may orient a textual discourse. It is a phenomenological model because meaning is generated by the interplay of linguistic and non-linguistic influences. In this instance, a semiotics of multimodality in discourse can prove its efficacy as it steers the reader primarily toward "a general syntax of discursive operations" in that the "universe of signification" is seen as a "praxis rather than as a stable set of fixed forms" of modalities.